PENGARUH GAYA KEPEMIMPINAN MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA PADA DINAS PEMBERDAYAAN MASYARAKAT DAN KAMPUNG DI KABUPATEN BERAU - Ayyub, Muh Amrizal; Hasnawati, Hasnawati (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2017)
ABSTRCAK The purpose of the research is whether the style is leadership, motivation and workplace influence the performance of the state civil apparatus thr / on the community empowerment and round kabaputen berau. Methods used in research is quantitative methods Judging from the results of the Hypothesis Test. Based on the results of Test F that is Fcount with a value of 10.750> from Ftable with a value of 3.26 there is an influence between the Independent X variable on the Dependent variable Y. From the results of the t test it is known that there is an influence between each independent variable on the dependent variable. Based on the Leadership Style variable, the value of tcount is 2,291> from the value of t table 2,02534, it can be seen that there is an influence between Variable X1 to Variable Y, then for Motivation variable with tcount 2,313> from the value of t table 2,02534 it can be seen that there is an influence between variable X2 to variable Y, then the Work Environment variable with tcount 2.447> from the value of t table 2.02534, it can be seen that there is an influence between variables X3 to variable Y. Keyword :Syle of leadership, motivation and work environment